Problem-Based Learning E-Book for Natural and Social Sciences in Fourth-Grade of Elementary Schools - Ardika, Gede; Sukmana, Adrianus I Wayan Ilia Yuda; Sudarma, I Komang (Universitas Pendidikan Ganesha, 2024)
This study was motivated by the low achievement levels of students in the Natural and Social Sciences (IPAS) subject. This issue arises from the lack of instructional materials that adequately support the learning process. The research aims to develop a problem-based learning e-book for fourth-grade IPAS in elementary schools. This is a development study employing the ADDIE model, which consists of five systematic stages: analysis, design, development, implementation, and evaluation. The study involved three experts (content, design, and media) and nine students in a small-group trial. Data collection methods included interviews, observations, questionnaires, and tests. Data analysis employed qualitative and quantitative techniques, as well as inferential statistics. The results indicated that the e-book achieved